Application of Video Media to Improve Student Learning Outcomes in Class III Thematic Learning for Natural Science Subjects at SDN 3 Bukit Tunggal - Putra, Chandra Anugrah; Witari, Sariya (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Background: This research is a phenomenon that is common today, namely low interest in learning, and motivation of students, as well as inadequate learning outcomes. Aim: The main aim of this research is to improve student learning outcomes. Method: The research method used in this research is classroom action research. Data sources in this research consisted of the school principal, homeroom teacher and students. Data collection techniques used include planning, implementation, observation, reflection, and documentation. Research data analysis was carried out through stages consisting of collecting lesson plans, questions, pre-test, and post-test results, as well as drawing conclusions, and verification. Result and Discussions: The research results show that the factors that influence the improvement in student outcomes are: (1) Student learning activities when learning science using video media achieve predetermined indicators of success. This shows that students are active in the learning process. (2) There is an increase in student learning outcomes when learning science using video media. Data and test results at the pre-action stage showed an average score of 75.83, with a classical completion level of 79.17%. In cycle I, student learning outcomes increased with an average score of 83.55% and a classical completion level of 95.83%. This has achieved the researchers’ established indicators of success, namely student learning outcomes with a KKM of 65, and a classical completion level of 85%.